Expression of Circulating miR-21 and -29 and their Association with Myocardial Fibrosis in Hypertrophic Cardiomyopathy - Angelopoulos, Andreas; Oikonomou, Evangelos; Antonopoulos, Alexios; Theofilis, Panagiotis; Zisimos, Konstantinos; Katsarou, Ourania; Gazouli, Maria; Lazaros, George; Papanikolaou, Paraskevi; Siasos, Gerasimos; Tousoulis, Dimitris; Tsioufis, Konstantinos; et al. (Current Medicinal Chemistry, 2024)
Background: Hypertrophic Cardiomyopathy (HCM) is characterized by myocardial hypertrophy, fibrosis, and sarcomeric disarray. Objective: To evaluate the expression levels of circulating miR-21 and -29 in patients with HCM and their association with clinical characteristics and myocardial fibrosis. Methods: In this case-control study, 27 subjects with HCM, 13 subjects with hypertensive cardiomyopathy, and 10 control subjects were enrolled. Evaluation of patients’ functional capacity was made by the six-minute walk test. Echocardiographic measurements of left ventricle systolic and diastolic function were conducted. Cardiac magnetic resonance late gadolinium enhancement (LGE) -through a semiquantitative evaluation- was used in the assessment of myocardial fibrosis extent in HCM patients. The expression of miR-21 and -29 in peripheral blood samples of all patients was measured via the method of quantitative reverse transcription polymerase chain reaction. Results: Circulating levels of miR-21 were higher in both hypertensive and HCM (p<0.001) compared to controls, while expression of miR-29 did not differ between the three studied groups. In patients with HCM and LGE-detected myocardial fibrosis in more than 4 out of 17 myocardial segments, delta CT miR-21 values were lower than in patients with myocardial LGE in 3 or fewer myocardial segments (2.71 ± 1.06 deltaCT vs. 3.50 ± 0.55 deltaCT, p<0.04), indicating the higher expression of circulating miR-21 in patients with more extensive myocardial fibrosis. Conclusion: MiR-21 was overexpressed in patients with HCM and hypertensive cardiomyopathy. Importantly, in patients with HCM, more extensive myocardial fibrosis was associated with higher levels of miR-21.
Keywords: echocardiography